Tindak Pidana Pencurian Benda Sakral dalam Putusan Pengadilan di Wilayah Hukum Pengadilan Tinggi Bali - Setiawan, I Gusti Ngurah Oka Putra (Jurnal Cakrawala Hukum, 2018)
Theft of sacred objects (pratima) that occur in the jurisdiction of Bali lately is very disturbing to the Balinese people. Because for the Balinese people who are Hindus, the theft of sacred objects (pratima) has a negative effect on everyday life which results in disruption of the balance between real (sekala) and supernatural (niskala). This type of writing is normative juridical or dogmatic legal sciences. In the process of resolving cases of theft of sacred objects (pratima), judges use Article 362 of the Criminal Code (KUHP) as a guideline for imposing penalties on perpetrators. In the view of Balinese people who are Hindus, the perpetrators should be given additional penalties in the form of customary sanctions so that the perpetrators know that the actions committed are fatal and can result in imbalances in the realm of the village where they commit theft, because to restore imbalances These Balinese people who are Hindus must prepare a very large ceremony (upakara) in the form of preparing offerings or offerings called (prayascitta).How to cite item:Â Setiawan, I. (2018). Tindak Pidana Pencurian Benda Sakral dalam Putusan Pengadilan di Wilayah Hukum Pengadilan Tinggi Bali.Â Jurnal Cakrawala Hukum, 9(1), 79-88. doi:https://doi.org/10.26905/idjch.v9i1.2618